Binding affinity and antioxidant activity of the complex of (‐)‐epigallocatechin‐3‐gallate and whey protein isolate: Effect of ultrasound pretreatment. (30th April 2019) - Chen, Weijun; Wang, Haiyang; Wang, Wenjun; Ma, Xiaobin; Guo, Mingming; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: The binding affinity of whey protein isolate (WPI) for (‐)‐epigallocatechin‐3‐gallate (EGCG) and the antioxidant activity of the formed complexes as influenced by ultrasound pretreatment were investigated. After treated by ultrasound at 200 W for 20 min, the apparent binding constant and the number of binding sites could be increased by 10.92 times and 23.05%, respectively. This indicated that ultrasound pretreatment did enhance the binding interaction between WPI and EGCG. Ultrasound pretreatment could increase the random coil content, cause the molecular unfolding and expose more hydrophobic groups inside the molecules to be exposed to the surface. These ultrasound‐induced conformational changes observed in WPI might account for its enhanced binding affinity for EGCG. Moreover, complexing with WPI could protect EGCG antioxidant activity and better protection was observed for that of ultrasound pretreated WPI. This study confirmed that ultrasound pretreatment could help the design of WPI based delivery system for EGCG. Practical applications: Due to its good ligand‐binding properties, whey protein isolate (WPI) have great potential being used as a protective carrier for (‐)‐epigallocatechin‐3‐gallate (EGCG) via the formation of WPI‐EGCG complexes. As a relatively low‐cost, nonhazardous, and ecofriendly technique, ultrasound has been widely applied in the modification of WPI. However, the interaction between WPI and EGCG as influenced by ultrasound pretreatment is still unknown. In this study, the effects of ultrasound pretreatment on binding capacity of WPI for EGCG and the antioxidant activity of the formed complex were investigated. The results showed that the binding interaction between WPI and EGCG could be enhanced by ultrasound pretreatment. Moreover, complexing with WPI could provide preservation of EGCG antioxidant activity and better protection were obtained by complexing EGCG with ultrasound pretreated WPI. These results were helpful for the utilization of WPI as a protective vehicle for EGCG and other polyphenols in food industry.